A new performance analysis model for urban water supply systems evaluation - Kızılöz, Burak; Şişman, Eyüp (Desalination Publications, 2021)
Non-revenue water (NRW) is among the performance indicators that have a great importance in urban water distribution systems. In this study, the probability statistical approach used to compare the temporal variations of the non-revenue water rate (NRWR) and a new performance evaluation chart have been suggested for practical use of the NRWR. The NRWR's probabilistic occurrence frequency and the statistical analysis provide a criterion for the performance evaluation and improvement of operating conditions. The NRWR performance indicator evaluation has been made for three periods of 12 districts in Kocaeli by considering the risk level. According to the study results, in the 2013-2015 periods, the performance of the Dilovasi, Gebze, and Kartepe districts has improved significantly compared to the 2010-2012 periods. Basiskele and Izmit have the highest performance level in the last period following Kandira. It will be possible to ameliorate the NRWR of districts in the future periods through the suggested site-specific model analysis and prioritize the plans by sampling the good district practices.
Keywords: Urban Water Supply Systems; Performance Analysis; Model